Bending and Pressurisation Test of the Human Aortic Arch: Experiments, Modelling and Simulation of a Patient-Specific Case - Garcia-Herrera, C; Cruchaga-Ssa., M (2013)
This work presents experiments, modelling and simulation aimed at describing the mechanical behaviour of the human aortic arch during the bending and pressurisation test. The main motivation is to describe the material response of this artery when it is subjected to large quasi-static deformations in three different stages: bending, axial stretching and internal pressurisation. The sample corresponds to a young artery without cardiovascular pathologies. The pressure levels are within the normal and hypertension physiological ranges. The two principal findings of this work are firstly, the material characterisation performed via tensile test measurements that serve to derive the material parameters of a hyperelastic isotropic constitutive model and, secondly, the assessment of these material parameters in the simulation of the bending and pressurisation test. Overall, the reported material characterisation was found to provide a realistic description of the mechanical behaviour of the aortic arch under severe complex loading conditions considered in the bending and pressurisation test. © 2013 Taylor & Francis.